Assessment of antioxidative and selenium status by seleno‐dependent glutathione peroxidase activity in different blood fractions using a pig model: issues for clinical nutrition and research. Issue 1 (17th March 2017) - Dalto, D. B.; Lapointe, J.; Matte, J.‐J.
Summary: Blood seleno‐dependent glutathione peroxidase (SeGPX) activity is widely used as a metabolic indicator of systemic antioxidative status despite inconsistent responses in the literature. This study aimed to compare SeGPX activity profiles in different blood fractions, expressed with different reference units, and assess their impact on interpretation of results. Two studies on selenium (Se) metabolism in gilts, including long‐term and peri‐oestrus SeGPX activity profiles, were submitted to analysis of variance with double repeated measures, after data set standardization. Differences between studies were experimental period (three post‐pubertal oestrus or five post‐pubertal oestrus +30 days of gestation) and sample type (whole blood or blood plasma). No difference was observed between whole‐blood long‐term profiles (three oestrus) for SeGPX activity/mg haemoglobin (SeGPXhb) vs. SeGPX activity/ml whole blood (SeGPXwb; p = 0.29). No long‐term difference was observed in whole blood between profiles according to dietary Se provision (basal and dietary Se‐supplemented groups; p ≥ 0.12). Blood plasma long‐term profiles (five oestrus + 30 days gestation) for SeGPX/mg blood plasma protein (SeGPXpro) were different from SeGPX/ml blood plasma (SeGPXpla) according or not to Se provision (p ≤ 0.007 and p < 0.001 respectively). However, regardless of Se provision (p ≥ 0.80), when excluding gestation from the model, blood plasma profiles were similar. During the peri‐oestrus period (day −4 to +3), regardless of Se provision, SeGPX activity profiles differed according to reference units in both studies (p < 0.001). However, considering Se provision, similar profiles were observed in whole blood and blood plasma (p ≥ 0.27) for basal Se groups, whereas in Se‐supplemented groups they differed for both sample types (p ≤ 0.02). In conclusion, reference units influence interpretation of SeGPX activity according to physiological state. During oxidative stress periods, this effect depends upon dietary Se provision.